Steganography For Embedding Data In Digital Image - Sowan, Salah Ibrahem (2003)
The growth of the World Wide Web (WWW) has enabled the personal computer to be used as a general communications tool. As in the case of other forms of communication there is a wish for security and privacy. With literally millions of images moving on the Internet each year, it is safe to say that digital image Steganography is of real concern to many in the IT security field. Digital images could be used for a number of different types of security fear. In the business world, the sending of a harmless looking bitmap file could actually hide the latest company secrets. Steganography (literally, covered writing) is concealing of a secret message within another seemingly innocuous message, or carrier. Digital carriers include email, audio, and images. Steganography, like cryptography, is a means of providing secrecy. Steganography does so by hiding the very existence of the communication, while cryptography does so by scrambling a message so it cannot be understood. A cryptography message can be intercepted by an eavesdropper, but the eavesdropper may not even know the existence of a steganographic message. This thesis discusses the issues regarding Steganography and its application to multimedia security and communication, addressing both theoretical and practical aspects, and tackling both design and attack problems. In the fundamental part, we identify a few key elements of Steganography through a layered structure. Data hiding is concerned to be as a communication problem where the embedded data is the signal to be transmitted. The tradeoff for two major categories of embedding data using spatial domain and frequency domain will be discussed. In addition, we have found that unevenly distributed embedding capacity brings difficulty in data hiding. We propose a complete solution to this problem, addressing considerations for choosing constant or variable embedding rate and enhancing the performance for each case. In the design part, we present new data hiding algorithms for binary images, grayscale and color images, covering such applications as annotation, fingerprinting, and ownership protection.